Upaya Meningkatkan Kreativitas Anak Melalui Kegiatan Mewarnai Berbasis Kearifan Lokal Papua Di TK Melati Sanggar Kegiatan Belajar Merauke - Nike Ferolin Gebze; Diah Harmawati; Hariani Fitrianti (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The purpose of this study aims to find out the improvement with the application of coloring activities based on Papuan local wisdom for the 2022/2023 academic year. This research is a classroom action research and was carried out for 2 cycles. Each cycle consisted of 4 stages, namely planning, implementation, observation, and reflection. The research subjects were group B children of TK Melati Sanggar Merauke Learning Activities for the 2022-2023 school year, a total of 12 children consisting of of 6 boys and 6 girls. Data collection techniques used observation and documentation. The instruments used were observation sheets of children's creativity abilities and observation sheets of student and teacher activities. Data analysis used descriptive statistical data analysis. The results showed that through coloring activities based on Papuan local wisdom it could improve children's creative abilities. This could be shown from the success of learning in the minimal category of developing according to expectations or three stars increasing from 16.67% in pre-cycle to 83.33% in cycle I and 83 .33% in cycle II. In addition, there was also an increase in student activity with an active category of 50% in cycle I, an increase of 83.33% in cycle II, and teacher activity in the learning process increased with a good category of 85.71% in cycle I to 100% in cycle II. So it can be concluded that coloring activities based on Papuan local wisdom can improve creativity abilities in children aged 5-6 years at Melati Kindergarten, Merauke Learning Activity Center.